Human Resource Management and Employee Engagement in Nepalese Commercial Banks (Journal of Nepalese Business Studies, 2023)
Employee Engagement is mainstream attention for any type of organizations in the current business scenario. The aim of this study is to examine the relationship between employee engagement and HRM components among employees of various commercial banks in Nepal. The workplace, values, motivation, and attitude are among the independent variables in the study. Employee engagement is the study's dependent variable. Descriptive research design is the one employed in this study. The study's population consisted of 46,508 employees, and 396 employees were randomly chosen from 11 commercial banks using a simple random sampling technique. A standardized Likert scale questionnaire was used to collect the data, with 1 denoting a strong disagreement and 5 denoting a strong agreement. The data were analyzed using regression analysis, correlation, and descriptive statistics. Cronbach's Alpha has been used to measure reliability. With an average Chronbach's Alpha rating of 0.79, reliability has been considered acceptable. The study has concluded that employees' attitude, motivation and value have a favorable and significant relationship with employee engagement, Workplace has a positive but insignificant impact on employee engagement. The main emphasis of this study is the need for proactive, comprehensive strategies to human resource management techniques in order to guarantee coherence with company goals and prioritize employee engagement.